Analisis Pengelolaan BUMDES Dalam Upaya Meningkatkan Kesejahteraan Masyarakat - Majojo, Muhammad Yasin (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to find out how the Management of Village Owned Enterprises in Balbar Village, find out the Welfare of the Balbar Village Community, and also the obstacles faced by Bumdes Berkah, this research took place in Balbar Village, North Oba District, Tidore Islands City, North Maluku Province, the research was conducted on November 4, 2022.This research is a descriptive qualitative research, and the methods used in data collection are: observation, interviews, and documentation, with a total of 7 informants.The results of the research are (1) The management of Bumdes Berkah in Balbar Village has been well managed and has fully implemented the management principles (2) Village-owned enterprises (umdes Berkah) have a significant effect on increasing the welfare of the people in Balbar Village because there are still units other Bumdes business units that are still active, the role of Bumdes related to income has been able to fulfill the needs of other communities (3) The constraints faced by Bumdes Berkah in operational costs and lack of human resources, it is very necessary to have training to improve human resources, the operational costs of the Bumdes waste management business unit require large capital to operate again, so the role of the related government is very important in the waste business